2018
DOI: 10.1111/iju.13552
|View full text |Cite
|
Sign up to set email alerts
|

Chronological changes in the epidemiological characteristics of upper urinary tract urolithiasis in Japan

Abstract: Objectives: To assess epidemiological and chronological trends of upper urinary tract stones in Japan in 2015.Methods: Patients with a first episode of upper urinary tract stones in 2015 were enrolled in this nationwide survey. The study included all hospitals approved by the Japanese Board of Urology, therefore covering most of the hospitals where urologists practice in Japan. The annual incidence and composition of urolithiasis were evaluated by age and sex. These results were compared with the previous resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 18 publications
1
45
1
Order By: Relevance
“…The annual incidence of upper tract urolithiasis in Korea was estimated to be 457.02 per 100 000 in the overall population, with 589.09 per 100 000 men and 326.64 per 100 000 women . In Japan, the estimated annual incidence of a first‐episode upper urinary tract stone in 2015 was 137.9 (191.9 in men and 86.9 in women) per 100 000 . In Taiwan, the prevalence of urolithiasis was 7.4% in 2010, and these results were similar to those in Western countries …”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…The annual incidence of upper tract urolithiasis in Korea was estimated to be 457.02 per 100 000 in the overall population, with 589.09 per 100 000 men and 326.64 per 100 000 women . In Japan, the estimated annual incidence of a first‐episode upper urinary tract stone in 2015 was 137.9 (191.9 in men and 86.9 in women) per 100 000 . In Taiwan, the prevalence of urolithiasis was 7.4% in 2010, and these results were similar to those in Western countries …”
Section: Introductionmentioning
confidence: 64%
“…Sakamoto et al . reported that the proportion of patients receiving SWL decreased to 60.4% in 2015 compared with 91.2% in 1995 . In contrast, a remarkable increase was observed in the proportion of patients receiving PNL and/or URS in the past 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the increased incidence of upper urinary tract stones might reflect the increased incidence of lower urinary tract stones. Based on the epidemiology of upper urinary tract stones in Japan, the incidence of upper urinary tract stones increased from 43.7 per 100 000 to 137.9 per 100 000 between 1965 and 2015 . Furthermore, an increased composition of calcium oxalate stone among lower urinary tract stones might also support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…We collected data regarding lower urinary tract stones from four published nationwide surveys of urolithiasis . The materials and methods applied in the surveys are described elsewhere . In brief, questionnaires were posted to 1210 hospitals in January 2015 to estimate the total number of Japanese patients with stones, and 459 of them responded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation